Hierarchical Ti3C2Tx@ZnO Hollow Spheres with Excellent Microwave Absorption Inspired by the Visual Phenomenon of Eyeless Urchins - Wang, Yan‑Qin; Zhao, Hai‑Bo; Cheng, Jin‑Bo; Liu, Bo‑Wen; Fu, Qiang; Wang, Yu‑Zhong (Nano-Micro Letters, 2022)
Ingenious microstructure design and rational composition selection are effective approaches to realize high-performance microwave absorbers, and the advancement of biomimetic manufacturing provides a new strategy. In nature, urchins are the animals without eyes but can “see”, because their special structure composed of regular spines and spherical photosensitive bodies “amplifies” the light-receiving ability. Herein, inspired by the above phenomenon, the biomimetic urchin-like Ti3C2Tx@ZnO hollow microspheres are rationally designed and fabricated, in which ZnO nanoarrays (length: ~ 2.3 μm, diameter: ~ 100 nm) as the urchin spines are evenly grafted onto the surface of the Ti3C2Tx hollow spheres (diameter: ~ 4.2 μm) as the urchin spherical photosensitive bodies. The construction of gradient impedance and hierarchical heterostructures enhance the attenuation of incident electromagnetic waves. And the EMW loss behavior is further revealed by limited integral simulation calculations, which fully highlights the advantages of the urchin-like architecture. As a result, the Ti3C2Tx@ZnO hollow spheres deliver a strong reflection loss of − 57.4 dB and broad effective absorption bandwidth of 6.56 GHz, superior to similar absorbents. This work provides a new biomimetic strategy for the design and manufacturing of advanced microwave absorbers. Highlights: 1 Inspired by the photoreception mechanisms of urchins, the urchin-like Ti3C2Tx@ZnO hollow spheres are rationally designed as high-performance microwave absorbents by constructing ZnO nanoarrays onto the surface of Ti3C2Tx hollow spheres. 2 Both experimental and theoretical simulation results demonstrate that the microstructure of urchin-like possesses giant advantages in electromagnetic wave absorption performance, which is superior to most absorbers with similar components.